IMPACT OF INCLINATION AND V-SHAPED RIBS ON FREE CONVECTION FROM INCLINED SQUARE AIR DUCT SUBJECTED TO LATERAL THERMAL FLUX: AN EXPERIMENTAL STUDY (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
This study experimentally investigates natural convection heat transfer in an inclined rectangular duct with a square cross-section. The effects of inclination angles (30°, 45°, and 60°) and v-shaped ribs on the performance of heat transfer are examined under steady-state conditions at a heat flux varying from 63.45 W/m² to 634.52 W/m². The modified average Rayleigh number (Ra*) ranges from 11.5×106 to 10.56×107 and a. The results indicate that increasing the inclination angle and adding ribs significantly enhance natural convection by intensifying turbulence and disrupting the thermal boundary layer. With increasing inclination angle and the introduction of V-shaped ribs, at 30o, 45o, and 60o, the ribbed duct showed heat transfer enhancements of 21.7%, 32.17%, and 48.15%, respectively, compared to the smooth duct. Furthermore, the local heat transfer increases with inclination angle and adding ribs.